Description of a new species of the "Haenydra" lineage (Coleoptera: Hydraenidae) from the Republic of Macedonia - Stanković, Vlatka Mičetić; Jäch, Manfred A. (Zootaxa, 2012)
A new species of Hydraena Kugelann, H. kucinici (Coleoptera: Hydraenidae), is described from the Republic of Macedonia. Taxonomic and faunistic notes on two closely related species, H. bosnica Apfelbeck and H. leonhardi Breit, are provided.